A predição do crescimento estatural na infância através de marcadores moleculares - Rodrigues, Albertina Gomes (2020)
A child´s stature growth is determined by a polygenic genetic inheritance. During childhood, several factors can modify the expected course of this development, such as a nutritional pattern, lifestyle, disease states. In countless situations, in front of a pediatric patient, the expectation of how the height velocity will be in height is extremely relevant: either in the introdution of a new therapy, or at what time to withdraw it. Still, in some situations, the identification of how the rhythm of longitudinal growth will be in the coming months can contribute to the diagnosis and decision making regarding this diagnosis. The identification of a marker that had a predictive character regarding growth woud be extremely relevant. Based on a transcriptome of adult individuals with a disease state (altered TSH), wich is very relevant in terms of heighy growth in childwood, the objetives of this study were: to select genes that could correlate with childhood growth and to associate the selected genes with growth in children included in this analysis. The measurement of the relative expression of 2 of the 5 genes selected by us (ADAMTS10 and IGF1_R), ajusted (logistic regression) by age and the measurement of plasma IGF-1 , managed to differentiate, in terms of the growth outcome, healthy children and adolescents. Furthermore, correlation was identified between all selected transcripts and HDL-C, a fact that may be associated with the role of HDL-C as a microRNA transporter or other interfering agents with action on mRNA.